Lovely, Dark and Deep: Robert Frost and His Most Famous Poem - Justin C. Cordova; James B. Young (Methodist DeBakey Cardiovascular Journal)
Robert Frost (1874-1963) had a lengthy and distinguished career as one of America’s favorite poets. “Stopping by Woods on a Snowy Evening” is perhaps his best-known work and was published as part of a collection that garnered him the first of his record-setting four Pulitzer Prizes in poetry. Though written in 1922, the poem continues to have relevance more than a century later. It is especially germane for members of the medical community, who have their own “promises to keep” in ensuring the best care possible for patients and their families, both now and in the future.